Effectiveness of oral versus intravenous tranexamic acid in primary total hip and knee arthroplasty: a randomised, non-inferiority trial. (February 2023) - DeFrancesco, Christopher J.; Reichel, Julia F.; Gbaje, Ejiro; Popovic, Marko; Freeman, Carrie; Wong, Marisa; DeMeo, Danya; Liu, Jiabin; Gonzalez Della Valle, Alejandro; Ranawat, Amar; Cross, Michael; Sculco, Peter K.; et al.
Abstract: Background: Tranexamic acid (TXA) reduces rates of blood transfusion for total hip arthroplasty (THA) and total knee arthroplasty (TKA). Although the use of oral TXA rather than intravenous (i.v.) TXA might improve safety and reduce cost, it is not clear whether oral administration is as effective. Methods: This noninferiority trial randomly assigned consecutive patients undergoing primary THA or TKA under neuraxial anaesthesia to either one preoperative dose of oral TXA or one preoperative dose of i.v. TXA. The primary outcome was calculated blood loss on postoperative day 1. Secondary outcomes were transfusions and complications within 30 days of surgery. Results: Four hundred participants were randomised (200 THA and 200 TKA). The final analysis included 196 THA patients (98 oral, 98 i.v.) and 191 TKA patients (93 oral, 98 i.v.). Oral TXA was non-inferior to i.v. TXA in terms of calculated blood loss for both THA (effect size=–18.2 ml; 95% confidence interval [CI], –113 to 76.3; P <0.001) and TKA (effect size=–79.7 ml; 95% CI, –178.9 to 19.6; P <0.001). One patient in the i.v. TXA group received a postoperative transfusion. Complication rates were similar between the two groups (5/191 [2.6%] oral vs 5/196 [2.6%] i.v.; P =1.00). Conclusions: Oral TXA can be administered in the preoperative setting before THA or TKA and performs similarly to i.v. TXA with respect to blood loss and transfusion rates. Switching from i.v. to oral TXA in this setting has the potential to improve patient safety and decrease costs.